Quantifying the fuel consumption, greenhouse gas emissions and air pollution of a potential commercial manganese nodule mining operation. (April 2020) - Heinrich, Luise; Koschinsky, Andrea; Markus, Till; Singh, Pradeep
Abstract: Manganese nodules contain economically valuable metals which may be mined in the future to supply metals to a growing world population. Thus far, environmental research has focused mainly on impacts occurring at the seafloor or in the water column but largely neglected any impacts caused above the sea surface. Emissions of greenhouse gases and other air pollutants contribute to, inter alia, global warming, acidification and photochemical ozone formation, which all negatively affect ecosystems and humans. We quantify the annual fuel consumption and emissions associated with a potential nodule mining operation in the Clarion-Clipperton Zone with an annual production of 3 million dry tons. We base the assessment on publicly-accessible energy demand estimates from three different studies and complement this with a calculation of the fuel demand and emissions of nodule transport scenarios to three different destinations. The global warming, acidification and photochemical ozone formation potentials range between 82, 600–482, 000 t CO2 -equivalent (-eq.), 1, 880–11, 197 t SO2 -eq., and 1, 390–8, 734 t NOx -eq., respectively, depending on factors including the engine loads, specific fuel oil consumption and transport speeds. We then discuss the regulatory dimension surrounding the topic. As three separate regimes (climate change, deep-sea mining and shipping) are applicable, we analyze the applicable framework and provide an outlook for the future regulation of DSM-related GHG emissions. Highlights: Calculation of emissions must be continuously refined during deep-sea mine planning. Emissions to air must be considered during deep-sea mine planning. It is necessary to consider all relevant policy regimes.